2009
DOI: 10.1203/pdr.0b013e3181b9b4bb
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein Supplementation Increases Peak Bone Mass Acquisition in Energy-Restricted Growing Rats

Abstract: Peak bone mass is a major determinant of osteoporosis pathogenesis during aging. Respective influences of energy and protein supplies on skeletal growth remains unclear. We investigated the effect of a 5-mo dietary restriction on bone status in young rats randomized into six groups (n ϭ 10 per group). Control animals were fed a diet containing a normal (13%) (C-NP) or a high-protein content (26%) (C-HP). The other groups received a 40% protein energy-restricted diet (PER-NP and PER-HP) or a 40% energyrestricte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
(51 reference statements)
2
10
1
2
Order By: Relevance
“…This difference might have been caused by the difference in the age of the rats. The age of the rat in the exercise and food restriction phase was lower in our study (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) weeks old) than in Dimarco et al's study (17-30 weeks old). Our findings could suggest that young female rats may be sensitive to the negative effects of the interaction of voluntary running exercise and food restriction.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This difference might have been caused by the difference in the age of the rats. The age of the rat in the exercise and food restriction phase was lower in our study (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) weeks old) than in Dimarco et al's study (17-30 weeks old). Our findings could suggest that young female rats may be sensitive to the negative effects of the interaction of voluntary running exercise and food restriction.…”
Section: Discussioncontrasting
confidence: 75%
“…Previous studies have reported that food restriction in sedentary female rats induces low BMD [12][13][14]. Furthermore, it has been reported that food restriction in female rats undergoing an exercise regimen induced low bone mineral content (BMC) [9,10] and BMD [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ten-week-old growing rats were fed an energy restricted diet or diet in which both protein and energy were restricted. When casein was supplemented to either one of these diets such that the percent of energy from protein equaled or exceeded that in a normal diet the animals demonstrated a significant protective effect against bone loss (Table 1, Mardon et al, 2009). BMD was lowest in animals that were placed on the energy and protein restricted diets compared to animals whose diets were solely calorically restricted.…”
Section: The Impact Of Dietary Protein On Bone Accretion During Grmentioning
confidence: 99%
“…The data are presented as the mean ± standard error of the mean, and data management and statistical analyses were performed with JMP 9.0.2 (SAS Institute Inc., Cary, NC, USA). The specific effects of Ovx and YCJ supplementation were examined by comparing values of the Sham, Ovx and Ovx+YCJ groups using analysis of variance and analysis of covariance with body weight as the covariate (26,27), with Tukey's honest significant difference (HSD) test. P<0.05 was considered to indicate a statistically significant difference.…”
Section: Peripheral Quantitative Computed Tomography (Pqct)mentioning
confidence: 99%